Tradisi Makkuliwa Lopi Pada Masyarakat Mandar Balanipa Dalam Perspektif Hukum Islam - Arhamarrahimin; Salenda, Kasjim (Universitas Islam Negeri Alauddin Makassar, 2022)
The focus of the research discussion is on: The history of the makkuliwa lopi tradition in the Mandar Mandar community in the Balanipa District, Polewali Mandar Regency, the process of implementing the makkuliwa lopi tradition in the Balanipa Mandar community, Polewali Mandar Regency and the perspective of Islamic law in the makkuliwa lopi tradition in the Balanipa Mandar community, Polewali Mandar Regency. This study shows that fishing traditions such as makkuliwa lopi by the Mandar Majene community have the intent and purpose of celebrating the new boat and asking for prayers for safety and blessings for the boat. The implementation of the tradition can take place at any time but the time and its implementation still take into account the time and day that are considered good. The perpetrators of this tradition are boat owners, local priests, boat builders and mustard (captain) boats. The implication of this research is that Mandar fishing traditions such as makkuliwa lopi need to be maintained and get more attention from the younger generation in order to know the diversity of local wisdom